Effect of two vs. three year harvest intervals on yields of Short Rotation Coppice (SRC) willow. (January 2022) - Johnston, Christopher R.; Walsh, Linda R.; McCracken, Alistair R.
Abstract: Five genotypes of Short Rotation Coppice (SRC) willow: 'Beagle' (( S. viminalis 'L810203' x viminalis 'L81102') x 'Astrid' x male parent unknown ), 'Olof' ( S. viminalis 'Bowles Hybrid') x (( S. schwerinii 'L79069') x (( S. viminalis 'L78195' x viminalis 'L78101') 'Orm') 'Bjorn'). 'Ashton Stott' (S.viminalis 'Bowles Hybrid') x S.dasyclados 'Korso', 'Tora' ( S. schwerinii 'L79069') x (( S. viminalis 'L78195' x viminalis 'L 7 8101' ) 'Orm'), and 'Torhild' (( S. schwerinii '79, 069') x (( S. viminalis ) x S. viminalis 'L78195' x viminalis 'L78101')) 'Orm') 'Tora') x ((S.viminalis 'L78195' x viminalis 'L78101') 'Orm') were grown in large mono-plots or within plots of intimate mixtures. Over a seven year period half of the plots were harvested on a two-year harvest cycle (three harvests) and the rest on a three-year harvest cycle (two harvests). At the end of this 7 year trial period there were no significant differences between total dry weights or stool survival, irrespective of harvest interval. With the realisation of the importance of this finding for more regular crop management practices, the experiment was continued for a further six years allowing for a further round of two and three year harvests. Results suggest that there ultimately are yield penalties, although these may be minimised by careful and appropriate clonal selection. Graphical abstract: Image 1 Highlights: Some varieties appear to be more resilient than others when harvested more frequently. 10% yield decline when harvesting more regularly over the twelve year assessment period. Variety has more of an effect on yield that harvesting regime.